Collagen in Health and Disease - Sandhu, Simarpreet V; Gupta, Shruti; Bansal, Himanta; Singla, Kartesh (Journal of Orofacial Research, 2012)
Collagen is the unique, triple helical protein molecule which forms the major part of the extracellular matrix. It is the most abundant protein in the human body, representing 30% of its dry weight and is important to health because it characterizes the structure of skin, connective tissues, tendons, bones and cartilage. As collagen forms building block of body structures, any defect in collagen results in disorders, such as osteogenesis imperfecta, Ehlers-Dalnos syndrome, scurvy, systemic lupus erythematosus, systemic sclerosis, Stickler syndrome, oral submucous fibrosis, Marfan syndrome, epidermolysis bullosa, Alport syndrome. This review discusses the role of collagen in health as well as disease.